Dehydrogenation of Alcohols and Hydrocarbons by Atomic Metal Anions. Issue 3 (June 2015) - Halvachizadeh, Jaleh; Mungham, Alex; Mayer, Paul M.
The reactivity of anionic metal–carbonyl systems toward hydrocarbons, alcohols, and a variety of other classes of molecules is well established in the literature. In this study we explored the reactions of atomic metal anions M −, notably K −, Cs −, Co −, Fe −, Cu −, and Ag −, with alcohols, alkanes, alkenes, and alkynes. All of the metal anions deprotonated the alcohols and alkynes. Also observed were the subsequent reactions of the resulting organic anions. Fe − and Cu − consistently displayed mono- and bis-dehydrogenation of primary and secondary alcohols, and alkanes, alkenes, and alkynes to form MH − and MH2 − . Mechanisms for the dehydrogenation reactions are proposed and substantiated with isotopically-labelled reagents and thermochemical arguments.